Caps on Political Lobbying: Comment - Kaplan, ToddR.; Wettstein, David (American Economic Review, 2006)
Following the 1999 Israeli elections, the winning candidate's (Ehud Barak's) party was fined 3.2 million dollars for violating Israel's campaign financing laws by exceeding the spending cap imposed and raising 1.2 million dollars illegally (see Time Europe, 2000).While adhering to the strict NCAA recruiting regulations, the University of Oregon spent 3 million dollars to make their football locker room the "best anywhere, including the NFL" (Lexington Herald Leader, 2003).When asked about the previous salary cap in the UK Football league, players said that "it [the cap] was so artificial that clubs paid money in brown paper envelopes."(BBC2, Newsnight 2002).In all these cases, there officially existed a rigid spending cap.However, they show that even though a cap exists: The cap might not be easily enforced.When enforced, the penalty may just be financial rather than a change in outcome.The cap may be enforced and adhered to, but there may also be alternate perhaps less effective (hence more costly) means of spending.We also see that the flexible nature of the cap is often built into the rules by examining the salary caps of the four major US sports leagues where the caps are routinely exceeded.In baseball and basketball, surpassing the cap invokes a pure financial penalty, called a luxury tax, which is proportional to the excess.In football, while the cap is stated in terms of salaries, many teams use signing bonuses as a way to circumvent it.In ice hockey, there is a dual cap system, where the luxury tax is invoked on salaries falling between the two caps and signing bonuses are an allowed method to exceed the